The Impact of Perceived Scientific and Social Consensus on Scientific Beliefs. Issue 1 (February 2018) - Kobayashi, Keiichi
Two studies examined perceptions of scientific and social (social network and public) consensus on scientific issues and their impact on scientific beliefs, using samples of Japanese people. In Study 1 ( N = 434), participants' estimates of scientific and social consensus predicted their scientific beliefs independently of each other. In Study 2 ( N = 694), the presentation of scientific and public consensus information as an anchor for consensus estimation influenced participants' scientific beliefs through their perceptions of scientific and public consensus. The perceived credibility of scientists had little if any effect on the relationship between perceived scientific consensus and scientific beliefs.